The planning of a territorial network among food, health and design - Pier Paolo Peruccio; Alessandra Savina (Agathón)
Today’s high-impact food production and consumption patterns are contributing to the loss of biodiversity and cultural identity, triggering irreversible change. This is why healthy nutrition, as the foundation of a socio-environmental balance, is considered transversally in the challenges suggested by the 2030 Sustainable Development Goals. The aim of this article is to investigate how the pursuit of better health at community level can be achieved through a multidisciplinary territorial project. The article describes the Cibo, Comunità e Salute project – developed by the Department of Architecture and Design of Politecnico di Torino and the CioCheVale Association – which has initiated a useful discussion between different stakeholders on the themes of food, health and sustainability, mediated and guided by systemic design.